Antithrombotic therapy and clinical characteristics of patients hospitalized for nonvalvular atrial fibrillation in Galician internal medicine clinics - Jose Manuel Cerqueiro-Gonzelez; Elena Fernandez-Bouza; Manuel Lorenzo Lopez- Reboiro; Paula Pesqueira-Fontan; Patricia Vazquez-Rodríguez; Ignacio Novo-Veleiro; Emilio Casariego-Vales (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
This was a multicenter, prospective, observational study that assessed the characteristics of patients with Nonvalvular Atrial Fibrillation (NVAF) admitted to internal medicine units in Galicia, Spain, as well as the antithrombotic treatment prescribed prior to hospital admission.